Overnight inpatient admission and revisit rates after pediatric adenotonsillectomy - Alsuhebani M; Walia H; Miller R; Elmaraghy C; Tumin D; Tobias JD; Raman VT (Dove Medical Press, 2019)
Mohammad Alsuhebani,1 Hina Walia,1 Rebecca Miller,1 Charles Elmaraghy,2,3 Dmitry Tumin,1 Joseph D Tobias,1,4 Vidya T Raman1,41Department of Anesthesiology & Pain Medicine, Nationwide Children’s Hospital, Columbus, OH, USA; 2Department of Pediatric Otolaryngology, Nationwide Children’s Hospital, Columbus, OH, USA; 3Department of Ear, Nose & Throat Surgery, The Ohio State University, Columbus, OH, USA; 4Department of Anesthesiology, The Ohio State University, Columbus, OH, USAObjective: Overnight admission may be necessary following adenotonsillectomy (T&A) in pediatric patients. This practice may reduce unplanned revisits following hospital discharge.Study design: Retrospective cohort study.Subjects: Children from the PHIS database.Methods: T&A performed in children during the years 2007–2015 were identified in the Pediatric Health Information System. The primary outcome was 7-day, all-cause readmission or emergency department (ED) revisit. Secondary analysis examined specific revisit types and 30-day revisits. The primary exposure was each institution’s annual rate of overnight stay after T&A.Results: The analysis included 411,876 procedures at 48 hospitals. Hospitals’ annual rates of overnight stay following T&A ranged from 3% to 100%, and 7-day revisit rates varied from 0% to 15%. The percentage or rate of 7-day revisits did not differ based on the use of overnight stay following T&A. At hospitals with higher overnight admission rates after T&A, 7-day revisits were more likely to take the form of inpatient admission rather than an ED visit.Conclusions: The current study confirms that pediatric hospitals vary widely in inpatient admission practices following T&A. This variation is not associated with differences in revisit rates at 7 and 30 days related to any cause. Although no mortality was noted in the current study, caution is suggested when deciding on the disposition of patients with comorbid conditions as risks related to various patients, anesthetic, and surgical-related issues exist. Risk stratification with appropriate identification of patients requiring overnight stay may be the most important for preventing acute care revisits after T&A.Keywords: tonsillectomy, emergency room visit, post-tonsillectomy hemorrhage, overnight admission, surgical complication